GitViz: An Interactive visualization system for analyzing development trends in the open-source software community - Park, Chanhee; Do, Sungjun; Lee, Eunjeong; Jang, Hanna; Jung, Sungchan; Han, Hyunwoo; Lee, Kyungwon (IEEE Pacific Visualization Symposium, 2019)
This study proposes a visualization that can assist computer scientists and data scientists to make decisions by exploring technology trends. While it is important for them to understand the technology trends in the rapidly changing computer science and data science fields, it takes considerable time and knowledge to acquire good information about these trends. Particularly, data/computer scientists with little experience in the field find it difficult to obtain information on such trends. Therefore, we propose a visualization system that can easily and quickly explore the technology trends in computer and data science. This study aims to identify the key technologies and developers in a specific field, and other technologies deeply related to specific technologies, and explore the changes in popularity of technologies, languages, and libraries over time. This study includes two case studies to obtain information using the proposed visualization. We demonstrate our system with GitHub repositories data.
Keywords: Computer scientists; Development trends; Interactive visualization systems; Open source software community; Radviz; Technology trends; Trends analysis; Visualization system; Decision making; Radviz; Trends analysis